Maturation and Bio-Banding in Youth Soccer Players: Insights from Turkish Male Academy across U-10 to U-15 Age - Seyed Houtan Shahidi; Atakan Çetiner; Ferhat Güneş; Joseph Isaak Esformes; Selçuk Karakaş (International Universities Strength and Conditioning Association, 2024)
Soccer academies are vital in identifying and nurturing young talent for senior-level competition. Relative age and biological maturation influence player performance and selection in youth soccer. While often grouped by Chronological Age (CA), variations within a CA category can lead to differences in maturation, with the Relative Age Effect (RAE) favoring older players' performance. Maturation, marked by physical and cognitive development, can significantly affect performance. Therefore, this study examined the interrelations between relative age, maturation status, and bio-banding in youth soccer players in U10 to U15 age cohorts. This study examined 60 male soccer players aged 10 to 15 (mean ± standard deviation; age: 12.6 ± 1.7 years; Weight: 49 ± 15.1 kg; Height: 157.2 ± 12.8 cm; sitting height: 69.7 ± 6.7 cm), assessing anthropometric measurements, maturation status, and physical performance. Players' physical attributes and performance levels were influenced by their maturation status rather than their relative age, with maturation-related disparities in strength and jump performance observed among age groups. Bio-banding, a strategy categorizing players by maturation status, created more equitable groups with homogenized physical attributes and performance. Early-maturing players showed advantages in physical attributes, while late-maturing players displayed enhanced leadership and self-confidence. Understanding maturation status is crucial for accurate performance assessment and equitable player grouping in youth soccer. This study underscores the significance of considering maturation status as a distinct determinant in evaluating young soccer players.